PERANCANGAN DAN PENERAPAN SISTEM MANAJEMEN MUTU ISO 9001:2015 DI PT. JAYABRIX INDONESIA, LAMONGAN, JAWA TIMUR - Angelin Fransiska Tanujaya; Eric Wibisono; Rahman Dwi Wahyudi (Perpustakaan Universitas Surabaya, 2018)
PT. Jayabrix Indonesia is a manufacturing company that produces ACC blocks and fiber cement boards, located in Lamongan, East Java. The vision of PT. Jayabrix Indonesia to become ACC Blocks and fiber cement boards producer that can penetrate the world’s market encourages the company to be certified ISO 9001:2008 in 2015. Because the active period will be expire in September 2018, PT. Jayabrix Indonesia encouraged to upgrade to ISO 9001:2015. This research aims to help the company to prepare for ISO 9001:2015. The result of gap identification shows that percentage of conformity is 76,6%, partial conformity is 18,8%, and nonconformity is 4,7%. Improvements that have been applied in PT. Jayabrix Indonesia are corrective action form, damage machine report, contract letter with supplier, and evaluation form of employee’s performance. The implementations and company’s quality obejctives are evaluated according to 7 principles of Quality Management System.